2001
DOI: 10.1039/b104139h
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of organic elemental analysis with flame photometry for sulfur determination at the nanogram level

Abstract: A new coupling of organic elemental analysis with flame photometric detection (OEA-FPD) was developed for the determination of total sulfur at nanogram levels. The method is based on the combustion of the sample under oxygen at high temperature, further reduction of the gases released, chromatographic separation and photometric detection. Combustion, chromatographic detection and coupling conditions are described and optimized. The new system is completely automated and fast (5 min per sample) and provides goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…GC‐FPD32 was used as the most suitable methodology for direct (i.e. without sample derivatization) S 2− detection at low concentrations, since it presents a quadratic response to compounds including one unique S atom 25. H 2 S was generated by strong acidification (H 2 SO 4 , pH 0.0) of the sample to ensure disruption of the metal–MT complex and to avoid precipitation of insoluble ZnS and CdS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GC‐FPD32 was used as the most suitable methodology for direct (i.e. without sample derivatization) S 2− detection at low concentrations, since it presents a quadratic response to compounds including one unique S atom 25. H 2 S was generated by strong acidification (H 2 SO 4 , pH 0.0) of the sample to ensure disruption of the metal–MT complex and to avoid precipitation of insoluble ZnS and CdS.…”
Section: Methodsmentioning
confidence: 99%
“…However, this method has serious drawbacks, as some degree of interference with cadmium ions has been reported24 and it is not suitable for samples containing copper owing to the insolubility of copper sulfide. As a consequence, we adapted a GC‐FPD (flame photometric detector) approach initially reported for solid samples 25. Both methods gave consistent results and permitted the mean S 2− ion content per MT to be determined (Table 1).…”
Section: Analytical Characterization Of Several Purified Metal–mt Aggmentioning
confidence: 99%
“…More recently, analytical techniques such as neutron activation analysis (Shukla et al 1978, Murty et al 1983, infrared absorption spectrometry (Terashima 1979(Terashima , 1988 and automatic elemental analyser (Din and Jones 1978, McGeehan and Naylor 1988, David et al 1989, Artiola 1990, Terashima 1993, Matejovic 1997, Kowalenko 2001) have been used. Coulometric titration (Atkin and Somerfield 1994), flame photometry (Marcó et al 2001), inductively coupled plasma-atomic emission spectrometry (ICP-AES, Okai et al 2001), high-resolution inductively coupled plasma-mass spectrometry (HP-ICP-MS, Makishima and Nakamura 2001), and elemental analyser-continuous flow isotope ratio mass spectrometry (EA-CFIRMS, Studley et al 2002) were reported as methods covering only S determination. Many data on the concentrations of C, H, N and S in geological reference materials have been reported, but not all international geochemical reference materials have certified values for these elements (e.g., , 1992, Govindaraju 1994, Imai et al 1996.…”
mentioning
confidence: 99%
“…After soil drying, the samples were sifted by using a 0.5 mm soil sifter. The nitrogen concentration of each sample was measured by using the Kjeldahl determination soil analysis method 27,28 . The measured values for all samples ranged from 0.056 to 0.289 wt %.…”
Section: Methodsmentioning
confidence: 99%
“…the troughs of the RMSEP curve) were selected into the discrete wavelength combination. Considering that some informative wavelengths are difficult to be found by simple linear regression and they always hide at the wavelengths with extreme values of RMSEP 28 , the peaks of the RMSEP curve should be added into the discrete wavelength combination. Therefore, 18 discrete-single wavelengths (the peaks and troughs with dash drop lines in Fig.…”
Section: Selection Of Discrete Wavelength Combination By Discrete Single-and-favorite Combination Linear Regression Methodmentioning
confidence: 99%